2016
DOI: 10.1111/and.12581
|View full text |Cite
|
Sign up to set email alerts
|

4-Methylcatechol inhibits cell growth and testosterone production in TM3 Leydig cells by reducing mitochondrial activity

Abstract: 4-Methylcatechol (4-MC) is a potential neuroprotective drug because it stimulates the synthesis of brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) in neurons. The present study explored the effect of 4-MC on cell growth and testosterone synthesis in the TM3 Leydig cells of mice. 4-MC did not enhance expression of both BDNF and NGF in these cells. However, this compound significantly inhibited cell proliferation and increased the number of apoptotic cells in a dose-dependent manner. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Several earlier studies applied MA-10 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], BLTK1 [ 20 , 35 ], or TM3 cells [ 48 , 49 , 50 , 51 ] to analyze effects of endogenous and exogenous substances on steroidogenesis by measuring T production using antibody-based methods. In most of these studies there is only limited information available on the specificity of the antibody used, and the commercial suppliers mostly included only a limited number of steroid metabolites in their characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies applied MA-10 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], BLTK1 [ 20 , 35 ], or TM3 cells [ 48 , 49 , 50 , 51 ] to analyze effects of endogenous and exogenous substances on steroidogenesis by measuring T production using antibody-based methods. In most of these studies there is only limited information available on the specificity of the antibody used, and the commercial suppliers mostly included only a limited number of steroid metabolites in their characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are very important for Leydig cell survival and testosterone production ( Kong et al, 2017a ). Previous studies have revealed that mitochondrial dysfunction of Leydig cells significantly reduced testosterone production and serum testosterone ( Li et al, 2017a ; Kong et al, 2017b ; Goncalves et al, 2018 ). Here, we found that triptolide activated the mitochondrial apoptosis pathway, increased cell ROS, and depolarized mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies reported that NGF and TrkA can stimulate sperm motility and induce sperm cell acrosome reactions. Furthermore, NGF plays an important role promoting testosterone production, proliferation and differentiation of Leydig cells [ 55 , 56 ]. Similar findings were also reported in human, monkey and rabbit.…”
Section: Discussionmentioning
confidence: 99%